Optimization of e-money and remittance service through cellular service business - Syarief, Syachrial; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2016)
Abstract - Inclusive Financial declaration by the Government of Indonesia since 2006 has been followed by an opportunity involvement of parties interested in developing digital financial services for the people of Indonesia. The aim of this thesis was to analyze the development opportunities of Indosatâ€™s financial services with brand name â€œdompetkuâ€ can grow through cooperation with distribution channels that had been done for the distribution of mobile products to customers throughout Indonesia. As of the time of this paper, distribution line that has been used in the cellular business has not become an alternative choice of developing e-money services and remittances. By using several framework analysis approaches like PESTEL Analysis, Porter 5 Forces Analysis and SWOT Analysis, then set out the partnership business model through the Business Model Canvas. To gain a deeper understanding and focus on the issue of the development of digital financial services, the authors use qualitative methods or qualitative data collection. Advantages of this method are the ability to present a complete description related to personal experiences that relate to a particular problem. Generally this is done with interviews, open-ended questions, or focus on a group. There are several factors that can influence the development of these digital financial services. Continuous evaluation of the regulations that apply in encouraging the development of financial inclusive is the key to get successful development of Digital Financial Services. According to Bank Indonesia Regulation Number 16 of 2014, author recommends to utilize "pulses" agent distribution channels and a modern shopping network with more attractive business model. Various risk factors that may arise should be anticipated through the development of risk analysis and mitigation. Â Keyword: digital financial service, financial inclusive, electronic money, e-money distribution channel, remittance.